2022
DOI: 10.3389/fcimb.2022.914684
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Mechanism of Bifidobacterium animalis B94 in the Prevention and Treatment of Liver Injury in Rats

Abstract: ObjectiveTo investigate the effect of Bifidobacterium animalis B94 on the prevention and treatment of liver injury in rats and to elucidate the underlying mechanism of this relationship.MethodsSpecific pathogen-free (SPF) rats were selected as the healthy control group, liver injury group and B94 treatment group, with 6 rats in each group. After the model was established, the experimental animals were tested for serum liver function indicators, gut microbiota composition, metabolite composition, and histopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A previous study reported the role of microbial therapy in reducing ALT levels in patients with nonalcoholic fatty liver disease (Loman et al, 2018). In addition, probiotic supplementation significantly reduced ALT levels and benefited liver injury in an animal model of acute liver injury and liver cirrhosis (Adawi et al, 2001;Liu et al, 2015;Liu et al, 2017;Zhang et al, 2022). In addition, treatment with probiotics prior to liver transplantation in cirrhotic patients was associated with improvements in early postoperative ALT (Grat et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported the role of microbial therapy in reducing ALT levels in patients with nonalcoholic fatty liver disease (Loman et al, 2018). In addition, probiotic supplementation significantly reduced ALT levels and benefited liver injury in an animal model of acute liver injury and liver cirrhosis (Adawi et al, 2001;Liu et al, 2015;Liu et al, 2017;Zhang et al, 2022). In addition, treatment with probiotics prior to liver transplantation in cirrhotic patients was associated with improvements in early postoperative ALT (Grat et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus and Bifidobacterium are typically beneficial bacterial genera. Bifidobacterium can exert nephroprotective effects through immunomodulation and also attenuate liver damage [ 35 , 36 ]. Cisplatin treatment induces the apoptosis of Lactobacillus , which may be the main reason for the significant decrease in the Lactobacillus level in the intestines of mice after cisplatin administration; restoration of intestinal Lactobacillus abundance is thought to be a favorable approach to repair cisplatin-induced oxidative stress and inflammatory damage in the liver and kidney [ 23 , 27 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…B94 with oral rehydration treatment significantly shortened the diarrheal period in acute rotavirus gastroenteritis infants/children (5 months to 5 years old), compared with control oral rehydration alone ( 40 ). In vivo study reported that B94 improved the gut microbiota and metabolic dysbiosis, thus reducing pathological abnormalities in gastrointestinal organs ( 43 ).…”
Section: Probiotic Research Against Infectious Disease In Pre-covid-1...mentioning
confidence: 99%